Loaded hip thrust-based PAP protocol effects on acceleration and sprint performance of handball players - Dello Lacono, A.; Padulo, J.; Seitz, L. D. (Journal of Sports Sciences, 2018)
This study aimed to investigate the acute effects of two barbell hip thrust-based (BHT) post-activation potentiation (PAP) protocols on subsequent sprint performance. Using a crossover design, eighteen handball athletes performed maximal 15-m sprints before and 15s, 4min and 8min after two experimental protocols consisting of BHT loaded with either 50% or 85% 1RM (50PAP and 85PAP, respectively), in order to profile the transient PAP effects. The resulting sprint performances were significantly impaired at 15s only after the 85PAP protocol, which induced likely and very likely greater decreases compared to the 50PAP. At 4min and 8min, significant improvements and very likely beneficial effects were observed in the 10m and 15m performances following both protocols. Significant differences were found when comparing the two PAPs over time; the results suggested very likely greater performance improvements in 10m following the 85PAP after 4min and 8min, and possible greater performance improvements in 15m after 4min. Positive correlations between BHT 1RMs values and the greatest individual PAP responses on sprint performance were found. This investigation showed that both moderate and intensive BHT exercises can induce a PAP response, but the effects may differ according to the recovery following the potentiating stimulus and the individual`s strength level.